The Seismicity Rate Model for the 2022 New Zealand National Seismic Hazard Model - Gerstenberger, Matt C.; Van Dissen, Russ J.; Rollins, Chris; DiCaprio, Chris; Chamberlain, Chris; Christophersen, Annemarie; Coffey, Genevieve L.; Ellis, Susan M.; Iturrieta, P.; Johnson, Katelyn M. (GNS Science, 2022)
This report summarises the Seismicity Rate Model (SRM) of the 2022 New Zealand National Seismic Hazard Model revision. The SRM is comprised of multiple component models that fall into one of two classes: (1) inversion fault model (IFM) or (2) distributed seismicity model (DSM). The full details of each component model are further detailed in reports specific to each component. The IFM uses an inversion-based method to model occurrence rates for hundreds of thousands of potential ruptures that have been constructed from the New Zealand Community Fault Model v1.0. The DSM supplements the IFM occurrence rate forecast with forecasts based on additional and complementary information. The DSM also models ruptures for faults that are currently unknown. The DSM consists of a hybrid model using multiple datasets and a uniform rate zone (URZ) model that forecasts rates for low-seismicity regions. The SRM produces an occurrence rate forecast for 100 years and includes over-dispersion of the rate variability when compared to Poisson. The over-dispersion is introduced both via the SRM logic tree and via the application of a negative binomial model in the URZ. In this report, we summarise the model components, the SRM logic tree and the sensitivity analyses that have been performed to reduce the size of the logic tree. (The authors)